Relationships among 5-HTT genotype, life events and gender in the recognition of facial emotions. - Antypa, N; Cerit, H; Kruijt, A; Verhoeven, F; Van der Does, A (2011)
Accumulating evidence has shown that a polymorphism in the promoter region of the serotonin-transporter (5-HTTLPR) modulates neural activation during the perceptual processing of emotional facial expressions. Furthermore, behavioral research has shown that attentional bias for negative information is increased in s allele carriers. We examined the interactions among 5-HTTLPR (including SNP rs25531), life events and gender on the detection of facial emotions. We found a main effect of genotype, as well as moderating effects of childhood emotional abuse (CEA) and recent life events (RLE). S homozygous participants recognized negative facial expressions at a lower intensity than the other genotype groups. This effect was more evident in female participants and in participants who had experienced life events. The 5-HTTLPR genotype affects facial emotional perception, a process which is linked to a neurobiological response to threat and vulnerability to emotional disorders.